Hemifacial Hyperplasia - Madhumita Srivastava; Sanjoy Chowdhury; Gaurav Vishal (Current Topics in Medicine and Medical Research Vol. 12, 2021)
Hemifacial hyperplasia, a congenital malformation symbolized by prominent unilateral overdevelopment of facial of the hard and soft tissues. The afflicted side grows swiftly than the non-affected side, creating a notable asymmetry that probably involves the skeleton and teeth, as well as all components of the associated soft tissues. Identified at birth, this disease progresses towards puberty and thought not to progress further. There is no single theory to explain the etiology adequately. Only deformities of facial tissues including teeth and their related tissues in the jaw, are key findings for correct diagnosis of CHH.